1987
DOI: 10.1159/000138294
|View full text |Cite
|
Sign up to set email alerts
|

Reversible, Narcotic-Associated Mental Status Impairment in Patients with Metastatic Cancer

Abstract: Pain and mental status were assessed in a series of 35 consecutive hospitalized patients with metastatic cancer receiving narcotics for pain that was difficult to control. Forty-five episodes of mental status impairment were detected in 27 of these patients. Fifteen patients had dose-related oversedation or organic brain syndrome. In only 4 could the narcotic dose be decreased without exacerbating the pain. Eleven patients had mental status impairment associated with factors other than the narcotic dose. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 7 publications
0
18
0
3
Order By: Relevance
“…39 In hospitalized cancer patients, who were on opioids and referred to a supportive care service, Leipzig et al found that 77% (27 of 35) experienced "impaired mental status" at least once when observed prospectively for a minimum of 7 days. 40 The impaired mental status was based on an impaired assessment on a brief modified portion of the Minimental State Examination. 41 The frequency of cognitive impairment on objective testing in patients with cancer on admission to a palliative care unit has been reported in the range of 20 -44%, 3,42-44 whereas 80 -90% show impairment before death.…”
Section: Prevalence and Pattern Of Cognitive Effects Associated With mentioning
confidence: 99%
See 2 more Smart Citations
“…39 In hospitalized cancer patients, who were on opioids and referred to a supportive care service, Leipzig et al found that 77% (27 of 35) experienced "impaired mental status" at least once when observed prospectively for a minimum of 7 days. 40 The impaired mental status was based on an impaired assessment on a brief modified portion of the Minimental State Examination. 41 The frequency of cognitive impairment on objective testing in patients with cancer on admission to a palliative care unit has been reported in the range of 20 -44%, 3,42-44 whereas 80 -90% show impairment before death.…”
Section: Prevalence and Pattern Of Cognitive Effects Associated With mentioning
confidence: 99%
“…The sensitivity and sophistication of neuropsychologic testing is variable, sometimes simple and crude 40 and at other times detailed and sophisticated. 18 Variability in opioid doses, choice of opioid, dosing intervals, administrative routes, and timing of neuropsychologic testing in relation to opioid administration also must be recognized.…”
Section: Prevalence and Pattern Of Cognitive Effects Associated With mentioning
confidence: 99%
See 1 more Smart Citation
“…macoterapia, particularmente se, entre as múltiplas medicações em uso, incluem-se drogas com ação anticolinérgica, anti-histamínica, sedativo-hipnóticos ou narcóticos, que conferem risco duas a três vezes maior para o desenvolvimento do delirium (Seymour e Pringle, 1983;Leipzig et al, 1987;Cantu e Korek, 1991).…”
Section: Introductionunclassified
“…Entre eles, desidratação (Levkoff et al, 1986), hipotensão peri-operatória, baixo débito cardíaco, hipóxia no pós-operatório e o uso de medicações com propriedades anticolinérgicas (Millar, 1981;Seymour et al, 1983;Williams et al, 1985b;Gustafson et al, 1988;Schor et al, 1992;Han et al, 2001). O tipo de anestesia (geral ou bloqueio raquimedular) parece não influenciar na incidência do delirium peri-operatório (Riis et al, 1983;Ghoneim, et al, 1988;Warren et al, 1990).…”
Section: Introductionunclassified